Heart-Protective Effects of Echinodorus grandiflorus in Rabbits That Are Fed a High-cholesterol Diet - Gasparotto, Francielly Mourão; Lívero, Francislaine Aparecida dos Reis; Palozi, Rhanany Allan Caloi; Ames, Maria Leticia; Nunes, Bruna; Donadel, Guilherme; Ribeiro, Rita de Cassia Lima; Lourenço, Emerson Luiz Botelho; Kassuya, Cândida Aparecida Leite; Junior, Arquimedes Gasparotto (Planta Medica, 2018)
Excess weight and dyslipidemia are among the most serious health problems in Western societies. These conditions enhance the risk of cardiac disease and have been linked with a higher prevalence of cardiac arrhythmias and sudden death. The present study investigated the cardioprotective effects of Echinodorus grandiflorus on ventricular remodeling in rabbits that were fed a 1% cholesterol-rich diet. We first obtained an ethanol-soluble fraction of E. grandiflorus and performed a detailed phytochemical study by liquid chromatography-DAD/ESI-MS. For 60 days, male rabbits were fed the cholesterol-rich diet or a diet without the addition of cholesterol. After 30 days, different groups of rabbits were treated with the ethanol-soluble fraction of E. grandiflorus (10, 30, and 100 mg/kg, p. o.), simvastatin (2.5 mg/kg), or vehicle once daily for 30 days. At the end of 60 days, the serum lipoprotein ratio, electrocardiographic profile, histopathological alterations, and the cardiac antioxidant defense system were investigated. Echocardiographic analysis showed morphological and functional alterations in cholesterol-rich diet-fed animals, indicating left ventricle hypertrophy. The total cholesterol/high-density lipoprotein ratio and low-density lipoprotein/high-density lipoprotein ratio were significantly higher in cholesterol-rich diet-fed rabbits. Myocardial flaccidity, fatty degeneration, and concentric left ventricular hypertrophy were observed. An increase in lipid peroxidation levels, a decrease in superoxide dismutase activity, and a decrease in reduced glutathione levels were observed in the myocardium of all cholesterol-rich diet-fed rabbits. Treatment with the ethanol-soluble fraction of E. grandiflorus, especially the highest dose, significantly reduced all of these alterations, thus demonstrating the cardioprotective effect of the ethanol-soluble fraction of E. grandiflorus on cardiac changes that are induced by a cholesterol-rich diet.
Keywords: Alismataceae; antioxidant; atherosclerosis; dyslipidemia; Echinodorus grandiflorus; ventricular hypertrophy